Bone mineral density in children with juvenile idiopathic arthritis after one year of treatment with etanercept - Sušić Gordana; Atanasković Marija; Stojanović Roksanda; Radunović Goran (Srpski Arhiv za Celokupno Lekarstvo, 2018)
Introduction/Objective. Juvenile idiopathic arthritis (JIA) is the most frequent chronic inflammatory, rheumatic disease of childhood, associated with disturbance of bone mineral metabolism, which develops gradually and progressively, and if untreated eventually leads to osteoporosis in adulthood. The aim of our study was to evaluate bone mineral density (BMD) in patients with JIA treated with etanercept over a period of one year. Methods. The prospective cohort study included 94 JIA patients (66 female, 28 male), their median age being 14.77 years. BMD was measured by dual-energy X-ray absorptiometry on the lumbar spine. Disease activity was assessed using the American College of Rheumatology Pedi 50 criteria. Results. After one year of treatment with etanercept, we found a statistically significant increment in all osteodensitometry variables (p < 0.001). Annual enhancement for the whole group was as follows: bone mineral content 15.8%, BMD 7.2%, BMDvol 4.2%. Z-score improved from -0.86 to -0.58 SD at the last visit, but decreased in rheumatoid factor-positive polyarthritis patients. Patients with systemic JIA had the lowest Z-score. Z-score correlated with functional disability level. BMD was lower in the group treated with glucocorticoids. Conclusion. Our results showed significant improvement of bone mineral density in children with JIA after one year of treatment with etanercept. Rheumatoid factor-positive and systemic JIA subtypes and treatment with glucocorticoids are the risk factors for impairing bone mineral metabolism.